Synthetic possessive identification “I” and “Not-I” in ancient Turkic affixes of belonging - Andirova А.; Kairzhanov А.К. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
This article examines the linguistic and historical-philosophical justification of the possessive thinking of the ancient Turks and the category of possessiveness in Turkic languages, formed by a synthetic morphological method, i.e., using possessive affixes. These affixes are genetically identical with the common Turkic means of derivation, distinguishing them from other languages, first of all, by the fact that they have "inalienable" properties of belonging, inherent only to the Turkic worldview of the most ancient times. Such an understanding of this category represents the relevance of the undertaken research. Therefore, the purpose of our article is to reveal the features of the possessive thinking of the ancient Turks, reflected in the possessive affixes and how both the person and the number of the subject of "inalienable" possession are expressed. This feature of the possessive affixes is a special feature of this category; it expresses not only the meaning of possessiveness, but also possessiveness in the broad sense of the word, formed as a result of the possessive identification of “I” and “Not-I” in the thinking of a Turkic person. The article analyzes a specific feature of the worldview of the nomads of the Great Steppe, associated with the means of expressing possessiveness, which appeared due to grammatical reflection, and preserved in all modern Turkic languages. It is determined that synthetism turned out to be the most appropriate means of expressing the meaning of possessiveness. We reveal the nature of the origin of the possessive affixes in the ancient Turkic language on the empirical material of the runic writing of the monuments of the Mountain and Southern Altai, as well as in the Orkhon-Yenisei monuments and in other single texts of the ancient Turks.